2011
DOI: 10.1002/cne.22536
|View full text |Cite
|
Sign up to set email alerts
|

A molecular mechanism that regulates medially oriented axonal growth of upper layer neurons in the developing neocortex

Abstract: During development, cortical neurons extend axons to their targets based on their laminar locations and cell types. Here we studied the molecular mechanism that regulates medially oriented axonal growth of upper layer neurons in the developing mouse cortex. Upper layer neurons were labeled with enhanced yellow fluorescent protein (EYFP) by in utero electroporation at E15.5. Cortical slices containing EYFP-labeled cells were dissected at E16, when axonal outgrowth from upper layer neurons is not initiated, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 69 publications
3
15
0
Order By: Relevance
“…The long-range guidance molecules are secreted by the midline glial populations, forming a concentration gradient and helping callosal axons pass through the CC with attractive (Figure 2(a)) and repulsive signals (Figures 2(b) and 2(c)). Slits [15, 24, 25], Wnts [26], Netrins [27, 28], Draxin [29], and Semaphorins [30] are some of the reported long-range guidance molecules. Recent studies have also clarified new roles for some of these guidance molecules.…”
Section: Callosal Axon Guidance By the Midline Structures During Dmentioning
confidence: 99%
“…The long-range guidance molecules are secreted by the midline glial populations, forming a concentration gradient and helping callosal axons pass through the CC with attractive (Figure 2(a)) and repulsive signals (Figures 2(b) and 2(c)). Slits [15, 24, 25], Wnts [26], Netrins [27, 28], Draxin [29], and Semaphorins [30] are some of the reported long-range guidance molecules. Recent studies have also clarified new roles for some of these guidance molecules.…”
Section: Callosal Axon Guidance By the Midline Structures During Dmentioning
confidence: 99%
“…Sema3A mRNA is expressed in the developing neocortex following the gradient from lateral-high to medial-low, and Npn1, the receptor of Sema3A is expressed on callosal axons extending from upper layer neurons [55]. Because Sema3A expressed ectopically suppresses the extension of callosal axons orienting medially, the gradient of Sema3A expression in the developing neocortex may be a mechanism in which callosal axons initially extend toward the midline from the developing neocortex [55]. To ask if the gradient of Sema3A exists in the developing neocortex of WT and KO mice under BALB/cAJ background, we analyzed the expression of Seam3A and Npn1 along the mediolateral axis of developing neocortex on E15.5–17.5.…”
Section: Resultsmentioning
confidence: 99%
“…The gradient of Sema3A expression from lateral-high to medial-low in the developing neocortex was observed in the region from developing neocortex to the midline of both WT and PlexinA1 KO mice, and Npn1+ axons extended medially from the lateral side in the brains of both genotypes (Fig 5). Previous studies have revealed the crucial roles of the Sema3A/Npn1 signal in the extension of callosal axons from the neocortex and axonal positioning in the CC during CC development [55, 59]. When axons of callosal projection neurons in the developing cortex initially begin to extend toward the midline, the gradient from high to low concentration of Sema3A may orient axons from the lateral to medial direction [55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations